Insights of Cannabinoid CBD: The Pharmacological Potential and Heterologous Expression - Pinto, Ingrid Batista; Mantovani, Cynthia; de Borba, Danrley Ramires dos Santos; Salina, Gabriela Beatriz; de Lima, Dênis Pires; Beatriz, Adilson (Orbital: The Electronic Journal of Chemistry, 2024)
In this review, a thorough approach was taken to the therapeutic potential of CBD and the possibilities of heterologous expression for its synthesis. Synthesizes the most recent discoveries on the medicinal benefits of CBD, its mode of action, and different methodologies that aim to maximize CBD production using heterologous expression systems. This review contributes to increasing knowledge about the wide range of uses of CBD and its potential in industries, including biotechnology and medicine.